Cytotoxicity, Antibacterial and Anti-Inflammatory Properties of A Synthesized Curcumin Analog and One of Its Novel Derivatives - Amir, Marian (AUC Knowledge Fountain, 2024)
This research aims to describe the synthesis, characterization, and the biological response via investigating the cytotoxic activity, hypoxic microenvironment response, antibacterial, and anti-inflammatory properties of the novel curcumin analog H-4073 and its succinate derivative (H-4073 SuD) in the context of hepatocellular carcinoma (HCC). The study also aimed to compare the effects of H-4073 and H-4073 SuD to assess their relative efficacy and potential as therapeutic agents. First, the cytotoxic effects of H-4073 and H-4073 SuD were evaluated on HEPG2 cell lines under normal conditions. Results revealed that H-4073 exhibited a significantly better cytotoxic effect than H-4073 SuD in normoxia. However, the investigation of the compounds' cytotoxic potential in a hypoxic microenvironment mimicking the cancerous conditions revealed that H-4073 SuD outperformed H-4073 in terms of cytotoxicity. This finding suggests that H-4073 SuD may be more effective in targeting HCC cells within the challenging physiological context of hypoxia. Another crucial aspect of this research was the assessment of the antibacterial and anti-inflammatory properties of both compounds. The results demonstrated that H-4073 SuD exhibited superior antibacterial and anti-inflammatory effects compared to H-4073. The enhanced antibacterial properties of H-4073 SuD highlight its potential in targeting bacterial infections associated with HCC, while its superior anti-inflammatory effects suggest its ability to modulate the inflammatory response within the tumor microenvironment more effectively. Finally, the safety evaluation of H-4073 and H-4073 SuD on human skin fibroblast cell lines (HSF) indicated that both compounds showed acceptable safety profiles. This finding further supports their potential as therapeutic candidates for HCC treatment. In conclusion, this research demonstrates the better cytotoxic effect of the novel curcumin analog H-4073 SuD compared to H-4073, particularly under hypoxic conditions. Additionally, H-4073 SuD exhibited enhanced antibacterial and anti-inflammatory properties compared to H-4073. These findings highlight the potential of H-4073 SuD as a promising therapeutic agent for HCC, offering 5 improved cytotoxicity, antibacterial activity, and anti-inflammatory effects. Further investigations are warranted to explore the underlying mechanisms and optimize the therapeutic potential of H-4073 SuD for the treatment of HCC.